2014
DOI: 10.1371/journal.pone.0101260
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion by Free Bisphosphonates and Zoledronate-Loaded Red Blood Cells

Abstract: Bisphosphonates, besides being important drugs for the treatment of various bone diseases, could also be used to induce apoptosis in macrophage-like and cancer cells. However, their activity in vivo is limited by a short plasma half-life and rapid uptake within bone. Therefore, several delivery systems have been proposed to modify their pharmacokinetic profile and biodistribution. Among these, red blood cells (RBCs) represent one of the most promising biological carriers. The aim of this study was to select th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 64 publications
0
30
0
1
Order By: Relevance
“…42 The toxicity of such effective antitumor associations cannot be ruled out in GBM patients and will need to be extensively investigated. Some studies have described that zoledronate, like some other bisphophonate molecules, might induce the depletion of macrophages 43 and act on microglia, 44 the main brain myeloid-immune cells. Then, to avoid the use of zoledronate it might be interesting to select particular Vg9Vd2 T cells that could naturally and specifically react more efficiently against GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…42 The toxicity of such effective antitumor associations cannot be ruled out in GBM patients and will need to be extensively investigated. Some studies have described that zoledronate, like some other bisphophonate molecules, might induce the depletion of macrophages 43 and act on microglia, 44 the main brain myeloid-immune cells. Then, to avoid the use of zoledronate it might be interesting to select particular Vg9Vd2 T cells that could naturally and specifically react more efficiently against GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chappard et al recently shown that both osteoclasts and activated macrophages act together to resorb β-TCP. Furthermore, there are many studies that bisphosphonates are effective in macrophage depletion (Rogers et al, 2013;Sabatino et al, 2014). Furthermore, there are many studies that bisphosphonates are effective in macrophage depletion (Rogers et al, 2013;Sabatino et al, 2014).…”
mentioning
confidence: 99%
“…Previously, using mice with subcutaneous B16-F10 tumors, we showed that the DOX-AS-M-PLGA-NPs can target tumors by interacting with TAMs, because depletion of mouse macrophages using zoledronic acid, a potent bisphosphonate known to induce macrophages to undergo apoptosis and is commonly used for the non-selective depletion of macrophages in mouse models [35, 36], decreases the distribution of DOX-AS-M-PLGA-NPs in tumors [26]. In addition, the DOX-AS-M-PLGA-NPs increase the uptake of the DOX by TAMs, as compared to DOX alone or DOX-AS-PLGA-NPs, which do not actively target TAMs due to the lack of surface-modification with mannose [26].…”
Section: Resultsmentioning
confidence: 99%